OPTIMALISASI REPRODUKSI SAPI POTONG: AKURASI DETEKSI BIRAHI, WAKTU IB, DAN PENCATATAN REPRODUKSI DI KELOMPOK SUMBER MULYO - Widyananda, Cepryana Sathalica; Efendi, Junaidi; Marheni, Diasyurannyta Adeputri (Universitas Mataram, 2025)
Efforts to increase production were carried out by applying artificial insemination methods, known as Artificial Insemination (AI). The standard for AI success is indicated by the S/C value. In Pamekasan Regency, the average S/C value was 2.8, which means that more than two, and even close to three, artificial insemination processes were required to achieve pregnancy. This value is still higher than the S/C standard, which is between 1.6 and 2.0. One of the reasons for this high S/C value is the low ability of farmers to detect oestrus and determine the right time for mating/AI. The problem faced by farmers in the ‘Sumber Mulyo’ Farmer Group is the lack of understanding or knowledge of farmers regarding the oestrus period of their livestock and the right time to mate their livestock. The community service activities will be carried out from August to October 2025. The methods to be used in this community service activity are (1) extension/socialisation, (2) demonstration/hands-on practice, (3) training, (4) discussion/question and answer session. These methods will be carried out in conjunction with the extension/socialisation, where the question and answer session will be used to evaluate the farmers' understanding of the material presented. This community service activity was attended by 30 farmers from the ‘Sumber Mulyo’ farmer group in Panagguan Village, Larangan Subdistrict, Pamekasan Regency. The results of the activity showed a significant increase in participants' understanding after attending the socialisation and assistance with oestrus detection. Based on the pre-test and post-test results, the average comprehension score increased from 1.15 to 1.96, or an increase of 0.81 points. The highest increase occurred in the indicator ‘timely oestrus detection can affect livestock productivity’ with a difference of 0.87 points, followed by understanding of ‘the oestrus cycle in cows’ by 0.83 points. These findings indicate that learning methods involving direct practice in the field are effective in improving farmers' ability to recognise signs of oestrus and determine the optimal mating time. Through these socialisation and mentoring activities, it has been proven to significantly improve farmers' understanding (p < 0.01), thereby potentially increasing reproductive success and livestock productivity.